Enhancing Preparedness for Arbovirus Infections with a One Health Approach: The Development and Implementation of Multisectoral Risk Assessment Exercises. (21st April 2020) - Dente, Maria Grazia; Riccardo, Flavia; Van Bortel, Wim; Marrama, Laurence; Mollet, Thomas; Derrough, Tarik; Sudre, Bertrand; Calistri, Paolo; Nacca, Gloria; Ranghiasci, Alessia; Escadafal, Camille; Gaayeb, Lobna; et al.
Abstract : Background . One Health is receiving attention for arbovirus infection prevention and control and for defining national "intersectoral" priorities. Increasing awareness of intersectoral priorities through multisectorial risk assessments (MRA) is promising, where data are not systematically shared between sectors. Towards this aim, the MediLabSecure project organized three MRA exercises (hereby called exercises): one on West Nile virus, one on Crimean–Congo haemorrhagic fever, and one on Rift Valley fever, assessing the added value of this approach. Methods . The exercises relied on RA methodologies of international organisations. Country representatives of the human and animal virology, medical entomology, and public health sectors (hereby called "sectors") involved in the surveillance of vector-borne diseases participated in the exercises. Background documentation was provided before each exercise, and a guide was developed for the facilitators. All three exercises included technical and methodological presentations and a guided RA directed at bringing into play the different sectors involved. To assess the added value of the approach, each participant was asked to rank the level of perceived benefit of the multisectoral collaboration for each "risk question" included in the exercises. Results . In total, 195 participants from 19 non-EU countries in the Mediterranean and Black Sea regions took part in the exercises. The participants assessed the multisectoral approach as valuable in analysing comprehensively the situation by having access to information and knowledge provided by each of the sectors involved. Sharing of information and discussion facilitated reaching a consensus on the level of risk in each country. Conclusions . Increasing awareness of intersectoral priorities, including cross-border ones, through MRA is relevant to reduce gaps due to unavailability of shared data and information. Given that six out of the ten threats to global health listed by WHO are occurring at the human-animal-environmental interfaces, comprehensive regional RA with a One Health approach made by national authorities can be a relevant added value for the global health security.